Therapeutic use of cannabidiol in companion animals. Perception of veterinary practitioners from Guayaquil, Ecuador - Rázuri Zambrano, Illona (2021)
The aim of the research was to determine the perception of veterinary practitioners in the city of Guayaquil regarding the therapeutic use of cannabidiol in companion animals. An anonymous and voluntary survey was conducted among veterinary professionals who completed their studies at the Agrarian University of Ecuador between 1992 and 2020 and who were working in the city of Guayaquil. In total, 305 valid surveys were obtained, of which 93% (286) stated that they agreed with the application of cannabidiol for therapeutic uses such as pain management, anxiety, musculoskeletal conditions, seizures, neoplasms and palliative care; they also indicated that the most accepted presentations are in the form of drinkable drops and tablets. Through the Chi square test, relationships were identified between the perception of the use of cannabidiol and the gender of the respondents in particular uses such as anxiety, seizures, phobia of thunder or fireworks, gastrointestinal diseases, neoplasms and anorexia. The research determined that the perception of most veterinary practitioners is positive regarding the use of cannabidiol as a therapeutic agent.